High Selective Mixed Membranes Based on Mesoporous MCM-41 and MCM-41-NH2 Particles in a Polysulfone Matrix - Miricioiu, Marius Gheorghe; Iacob, Ciprian; Nechifor, Gheorghe; Niculescu, Violeta-Carolina (Frontiers in Chemistry, 2019)
The development of membrane technology for gas separation processes evolved with the fabrication of so-called mixed matrix membranes (MMMs) as an alternative to neat polymers, in order to improve the overall membrane effectiveness. Once the mixed matrix membranes are used, the gas separation properties of the porous materials used as fillers are combined with the economical processability and desirable mechanical properties of polymer matrix. Mixed mesoporous silica/polymer membranes with high CO2 and O2 permeability and selectivity were designed and prepared by incorporating MCM-41 particles into a polymer matrix. Ordered mesoporous silica MCM-41 with high surface confirmed by BET analysis were obtained and functionalized with amino groups. In order to obtain the mixed membranes, the mesoporous silica was embedded into the polysulfone matrix (PSF). Flat mixed matrix membranes with 5, 10 and 20 wt% MCM-41 and MCM-41-NH2 loadings have been prepared via casting polymer solutions method. The phase’s interactions were studied using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transformed infrared spectroscopy (FTIR) and thermogravimetry (TGA), while the gas separation performances were evaluated using pure gases (CO2, O2, N2). The MCM-41/PSF and MCM-41-NH2/PSF membranes exhibited increased permeabilities for O2 (between 1.2-1.7 Barrer) and CO2 (between 4.2-8.1 Barrer) comparing to the neat membrane (0.8 Barrer). The loss of selectivity for O2/N2 (between 6-8%) and CO2/N2 (25-41%) gas pairs was not significant comparing with the pure membrane (8% and 39%, respectively). The MCM-41/PSF membranes were more selective for CO2/N2 than O2/N2 pair, due to the size difference between CO2 and N2 molecules and to the CO2 condensability, conducting to an increase of solubility. Stronger interactions have been noticed for MCM-41-NH2/PSF membranes due to the amino groups, the selectivity increasing for both gas pairs comparing with the MCM-41/PSF membranes.